Comparison of the beta-lactamase gene cluster in clonally distinct strains of Enterococcus faecalis. - Tomayko, J F (1996)
Ten beta-lactamase-producing Enterococcus faecalis isolates were examined for the presence of the staphylococcal beta-lactamase repressor and antirepressor genes. Four isolates, previously shown to be unrelated to each other by pulsed-field gel electrophoresis analysis, were positive for both genes by PCR, although beta-lactamase production was not induced with methicillin. Six isolates, previously shown to be clonally related, were negative for both genes by PCR. The blaZ sequences of eight beta-lactamase-producing E. faecalis isolates were determined. Seven isolates from five distinct clones had sequences identical to that previously reported for E. faecalis HH22, regardless of whether the repressor or antirepressor was demonstrated by PCR. However, blaZ from one isolate differed from those of the other enterococci by 11 nucleotides; this isolate is part of the large clone, as defined by pulsed-field gel electrophoresis and multilocus enzyme analysis, that includes HH22. These findings suggest either that enterococci have acquired the bla gene cluster from more than one source or that the gene cluster has undergone considerable change since acquisition by this clone.